THE MECHANISMS INHIBITING PYRUVATE- AND OXOGLUTARATE DEHYDROGENASE COMPLEXES IN MUSSELS - Semenova, Olga O.; Budnyak, Oleksander K.; Petrov, Sergiy A. (European Scientific Journal, ESJ, 2014)
Activity of purified pyruvate dehydrogenase and 2 - oksoglutarate dehydrogenase multienzyme complexes was studied and a quantity of free SH-groups in them being influenced by chlorides of cadmium, copper and lead was determined. The conducted research proved a considerable activity impairment of dehydrogenases of oxoacids and of the free SH – groups level.